1996
DOI: 10.1079/bjn19960043
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of endogenous and dietary urea in the large intestine of the mature horse

Abstract: The dynamics of N metabolism in mature horses were investigated when they were fed on a low-N diet or the same diet supplemented with sufficient urea or soyabean meal to meet their theoretical N requirements. There were no differences in DM, organic matter or neutral-detergent-fibre digestibilities for the three diets. N digestibilities and digestible-N intakes were similar for the urea-and soyabeansupplemented diets and very low for the low-N diet. For all three diets plasma urea was degraded in the digestive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
(7 reference statements)
1
14
2
1
Order By: Relevance
“…In this study, we attempted to link the microbial population to function using both targeted and nontargeted metabolic analysis. Ammonia measured in this study is somewhat higher than that reported (Hecker, 1971;Kern et al, 1974;Stott et al, 1983;Martin et al, 1996;Medina et al, 2002) with the exception of work by Wolter & Chaabouni (1979). Values obtained for VFAs (total and individual values) in this study are in agreement with the range previously reported in the literature (Hintz et al, 1971;Kern et al, 1973;Argenzio et al, 1974;Willard et al, 1977;Moore-Colyer et al, 2000;De Fombelle et al, 2003;Respondek et al, 2007;Daly et al, 2012).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In this study, we attempted to link the microbial population to function using both targeted and nontargeted metabolic analysis. Ammonia measured in this study is somewhat higher than that reported (Hecker, 1971;Kern et al, 1974;Stott et al, 1983;Martin et al, 1996;Medina et al, 2002) with the exception of work by Wolter & Chaabouni (1979). Values obtained for VFAs (total and individual values) in this study are in agreement with the range previously reported in the literature (Hintz et al, 1971;Kern et al, 1973;Argenzio et al, 1974;Willard et al, 1977;Moore-Colyer et al, 2000;De Fombelle et al, 2003;Respondek et al, 2007;Daly et al, 2012).…”
Section: Discussioncontrasting
confidence: 74%
“…Fermentation products in terms of VFAs and ammonia were analysed as specific metabolites, and FT-IR was utilised to give a more generalist view. Some ammonia is likely to be utilised by bacteria in the large intestine for growth and some potentially absorbed to be recycled to the small intestine (Bochröder et al, 1994;Martin et al, 1996). Ammonia measured in this study is somewhat higher than that reported (Hecker, 1971;Kern et al, 1974;Stott et al, 1983;Martin et al, 1996;Medina et al, 2002) with the exception of work by Wolter & Chaabouni (1979).…”
Section: Discussioncontrasting
confidence: 62%
“…As a result, there was an increase (P<0.01) in urinary nitrogen for data not scaled to body weight and data accounting for endogenous losses and scaled to body weight, as well as an increase (P < 0.05) in urinary nitrogen for data scaled to body weight and data accounting for endogenous losses but not scaled to body weight. Other research has also indicated little or no benefit to adding urea to the diet of horses (Godbee and Slade, 1981;Martin et al, 1996) and resulted in increased urinary nitrogen when urea was added (Glade and Biesik, 1986). …”
Section: Nitrogen Balance Accounting For Endogenous Losses and Scaledmentioning
confidence: 99%
“…Apesar de os melhores valores de digestibilidade da fração fibrosa terem sido obtidos com as dietas com casca de soja e casca de milho, estas dietas propiciaram também menores médias de digestibilidade para proteína bruta, provavelmente em razão da maior influência ou do aumento das perdas endógenas nas fezes, assim como da possível maior concentração de corpos microbianos oriundos de atividade fermentativa mais intensa na região do cecocólon dos animais alimentados com estas dietas (Figueiredo et al, 1999;Martin et al, 1996;Oliveira & Furtado, 2001;Oliveira et al, 2002). Como as dietas com casca de soja e casca de milho possuem menores teores de proteína e maiores teores de fibra, possíveis inferências sobre efeitos sinérgicos na digestibilidade dos nutrientes tornam-se plausíveis, pois indicam interatividade entre as características intrínsecas dos alimentos e mecanismos fisiológicos compensatórios no trato digestório dos animais (Swenson & Reece, 1996).…”
Section: Resultsunclassified